2013
DOI: 10.1016/j.jval.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Item-Level Psychometric Properties for a New Patient-Reported Psoriasis Symptom Diary

Abstract: The 16-item Psoriasis Symptom Diary demonstrated favorable psychometric properties and is a brief, useful tool for measuring patient-based symptoms and the impact of chronic plaque psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 34 publications
3
49
0
Order By: Relevance
“…[83][84][85][86] Nevertheless, our strategy ensures that the evidence obtained applies to patients with PsA as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…[83][84][85][86] Nevertheless, our strategy ensures that the evidence obtained applies to patients with PsA as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…The PSD is a 16‐item, psoriasis‐specific PRO measure with a 24‐hour recall period (Table ) . A total of seven items evaluate the severity of the key signs and symptoms of plaque psoriasis, including psoriasis‐related itching (item 1), stinging (item 3), burning (item 5), pain from skin cracking (item 7), pain (item 9), scaling (item 11), and alterations in skin color (item 13).…”
Section: Methodsmentioning
confidence: 99%
“…To identify subjects who experienced a significant change in their disease state over the course of treatment and who reported that they responded to treatment, a threshold, or responder definition – characterizing a meaningful change in the scores of the measure – should be determined. For the PSD, Strober and colleagues used two methods recommended in the final PRO guidance to establish responder definitions: the anchor‐based method, and cumulative distribution function (CDF) plots depicting the range of the change in scores by treatment arm . The proportion of patients in the Phase III studies who achieved the thresholds previously identified from the Phase II data for the PGIC anchor “a little better” was computed, and the CDF plots were used to facilitate the evaluation of treatment response across a range of potential responder definitions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable subjects during the 2-week period could be identified and the scores from the weekly intervals compared (using an intraclass correlation, for example). This approach is similar to how the test-retest reliability of a field-based ePRO assessment that is administered on the same dedicated device would be tested (see, eg, Strober et al 21 ).…”
Section: Addressing Scientific Questionsmentioning
confidence: 99%